Standardization of Pan Styles Urged - Unknown (Trinidad Guardian)
Pan Trinbago, the official body of the steelbandsmen, have been asked to have a conference with all tuners, leading arrangers , leaders and players, to discuss improvements to the steelband instrument. These improvements include reviewing existing designs and placement of notes, as well as the range, so that one or more style of pan can be adopted as a standard.
Keywords: Steel drum (Musical instrument) -- Standards -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Steel drum (Musical instrument) -- Quality control